Catch Phase of Front Crawl Compared to Arm Pull on Vasa Trainer - Mc Wha, M.; Froud, J.; Arndt, J. (1999)
The purpose of our study was to determine the quality of the Vasa Trainer as a cross training apparatus. It was evident through our research and our assessment of our data that the Vasa Trainer provides a great cross training for the catch phase because because motions are so similar to swimming in the water. As evidenced by the angle-angle diagrams and the position-time graphs, the body maintains relatively the same position as in the water as it does on the Vasa Trainer. In fact, the Vasa Trainer actually requires a high elbow position which is very important for an effective swimming stroke in the water. It was interesting that the range of motion for the elbow joint during both movements was the same. This was not expected because the general thought was that elbow position drops in the water. The elbow position on the Vasa Trainer is ideal. It can be used as a cross training method to help enforce high elbow position. The shoulder joint had a greater range of motion on the Vasa Trainer than in the water. Because of the constant resistance on the Vasa Trainer, the shoulder will not have to correct body position which will lead to full range of motion and painfree pulling on the Vasa.Stark differences in the data resulted only when comparing the swimming in the water to Vasa Trainer as a function of velocity over time. The swimming in the water movement had greater speed fluctuations where the Vasa Trainer had only small changes in the speed of the movement. This difference can be accounted for by the added resistance of the water which the body must fight to maintain a horizontal balance. Our study was limited by our lack of skill with the video equipment that made the analysis of an underwater stroke difficult. The joint markers were hard to see in the water which made the transition from the stroke to data points difficult. It would have been interesting to analyze stroke force because that would help to determine how effective the Vasa Trainer is as a cross training method. Toussaint et al (1992) notes "By changing the orientation of the hand the propulsive force acting on the hand is aimed successfully in the direction of the motion."